1982
DOI: 10.1080/03014468200005951
|View full text |Cite
|
Sign up to set email alerts
|

Increase in length of leg relative to trunk in Japanese children and adults from 1957 to 1977: comparison with British and with Japanese Americans

Abstract: The secular trends in height, sitting height and leg length in Japanese children have been studied by fitting Preece-Baines Model I curves to the annual mean values from ages five to 17 of school data collected in 1957, 1967 and 1977. The method provides estimates of final adult value, and of age of maximum annual increment. Between 1957 and 1977 the maximal increments in height, sitting height and leg length all became earlier, by about a year in boys and a little less in girls. Japanese now mature about a ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
192
6
9

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(235 citation statements)
references
References 6 publications
22
192
6
9
Order By: Relevance
“…By the age of 15 years, the differences in leg length became non-significant and one explanation is that it is the component of stature known to be responsible for the greater part of prepubertal height increases (12,15,16) . Our observation confirms the earlier report by Tanner et al (17) that the catch-up growth during adolescence probably occurs more in leg length than trunk length.…”
Section: Discussionsupporting
confidence: 93%
“…By the age of 15 years, the differences in leg length became non-significant and one explanation is that it is the component of stature known to be responsible for the greater part of prepubertal height increases (12,15,16) . Our observation confirms the earlier report by Tanner et al (17) that the catch-up growth during adolescence probably occurs more in leg length than trunk length.…”
Section: Discussionsupporting
confidence: 93%
“…The study showed that the growth performance of these Indian girls conformed to the 50th percentile of the NCHS standards till the 12th year, thereafter (between 12-18 years), increments in heights of Indian girls were significantly less than those of American girls, as represented by NCHS standards. Similar phenomenon has been noted in Japan [8]. It has been postulated that calcium deficiency could underline the differences with respect to adolescent growth of Indian and American girls.…”
Section: Discussionsupporting
confidence: 70%
“…Tanner et al (1982) pointed out that the Japanese secular height trend from 1957 to 1977 was driven almost entirely by an increase in leg length. Ali et al (2000) studied secular changes in Japanese leg length for birth cohorts from 1943 to 1978, showing a steep rise in leg length as a percentage of height from 1943 to 1968 but a plateau thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Tanner, Hayashi, Preece, and Cameron (1982) showed this to be due primarily to an increase in leg length, possibly arising from the shift from rice to a dairy‐based diet during the 1970s.…”
Section: Introductionmentioning
confidence: 99%